Novel Synthetic Approach to Arylboronates via Rhodium-Catalyzed Carbon–Cyano Bond Cleavage of Nitriles - Kinuta, Hirotaka; Kita, Yusuke; Rémond, Emmanuelle; Tobisu, Mamoru; Chatani, Naoto (Synthesis, 2012)
A new rhodium-catalyzed method for preparing arylboronates from aryl cyanides through the cleavage of carbon–cyano bonds is described. This unprecedented transformation of nitriles allows the use of a cyano group as a boryl equivalent and the regioselective introduction of a boryl group at a late stage of the synthesis.
Keywords: rhodium; catalysis; borylation; nitrile; C–CN bond cleavage